The Optimal Mix of Inflationary Finance and Commodity Taxation with Collection Lags - Dixit, Avinash (IMF Working Papers; Working Paper ;, 1990)
When there are collection lags in the tax system, inflation reduces the real revenues. This is often offered as an argument for less reliance on the inflation tax. But the optimal rates of other taxes should also be reconsidered in the light of collection lags. When this is done, the focus shifts from the revenues (which can be recouped by changing the rates of these taxes), to the associated costs of collection. In a benchmark case where the average costs of collection are constant, the optimal inflation tax is independent of the collection lag.